Determinants of academic performance of healthcare professional students in a medical university, Ajman, United Arab Emirates - Shahnaz Mohamed Wazil; Sathyapriya Nandagopal; Afreen Abdul Rahim Sanaullah; Liju Susan Mathew; Nermine Nosseir; Jayadevan Sreedharan; Jayadevan Sreedharan; Anusha Sreejith; Anusha Sreejith; Latifa Nabeel Alsaad; Latifa Nabeel Alsaad; Jayakumary Muttappallymyalil; et al. (Frontiers in Education)
BackgroundLearning environments, lifestyle habits, and personal and social factors can significantly influence the academic performance of healthcare professional students. Additionally, individual study approaches may impact their academic outcomes. Understanding these contributing factors is essential for supporting student success and optimizing educational outcomes.MethodsA cross-sectional study was conducted among 521 healthcare professional students aged 18 and above using a self-administered questionnaire. The survey collected data on socio-demographic characteristics, academic performance (measured by CGPA), learning environments, lifestyle habits, and personal and social influences. Data were analyzed using descriptive and inferential statistics via SPSS version 29.ResultsThe study revealed that age, nationality, course of study, and academic year were significantly associated with CGPA, while gender showed no significant association. Most students reported a preference for visual learning styles, the use of active recall as a study technique, and studying primarily at home. Key factors such as mental health status, home-based learning environments, and peer/family support were also significantly associated with higher academic performance.ConclusionMultiple factors, including learning styles, study techniques, learning environments, and personal and social influences—can positively or negatively affect the academic performance of healthcare professional students. Addressing these factors through targeted support programs and awareness initiatives is essential to foster academic success and well-being among students.